Gamified Intervention for Health Promotion of Families in Child Health Clinics: A Cluster Randomised Trial - Selänne, Laura (Sage, 2025)
Objectives
This study aimed to evaluate the effectiveness of the digital and gamified WellWe intervention on parental self-efficacy for healthy behaviours and mindfulness in parenting at the comprehensive health checks of 4-year-old children.
Methods
Two-arm cluster, randomised, controlled trial with a 4-month follow-up.The data were collected from parents of 4-year-old children. Cluster randomisation was done at the municipality level. Fifteen child health clinics within 4 municipalities located in Southwest Finland were randomly allocated to either an intervention (WellWe intervention) or a control group (usual care). The outcome measures included the Parental Self-Efficacy for Healthy Behaviours (PDAP) and Mindfulness in Parenting (MIPQ) questionnaires. Data were collected at baseline, after the intervention and at the 4-month follow-up.
Results
Initially a total of 110 parents (50 in the intervention and 60 in the control group) participated in the study. At the end of the study, there were 33 parents involved, with 12 in the intervention group and 21 in the control group. Parental self-efficacy and mindfulness in parenting showed no statistically significant difference between the groups or within the groups at the different time points.
Conclusions
The results of the study showed no difference between the intervention and the usual care. The commitment of the subjects was lower than expected. The intervention could be improved by placing a greater focus on engaging and motivating both families and public health nurses (PHNs). Therefore, when refining the intervention further, it's important to involve the target group more actively in the design of both content and delivery.